IMPLEMENTASI KEBIJAKAN TAMBAHAN PENGHASILAN PEGAWAI (TPP) DI PROVINSI BENGKULU - Susanto, Adi; Fachruzzaman, Fachruzzaman; Abdullah, Abdullah (UNIB Press, 2020)
The purpose of this study was to determine and analyze the implementation of the Employee Additional Income policy in Bengkulu Province. This type of research is descriptive qualitative. The type of data used is primary data obtained through interviews and documentation studies. Respondents or informants in the study were civil apparatus in Bengkulu Province Government recipients of Employee Additional Income. Data analysis method used is descriptive analysis and qualitative analysis. This study found that: (1) Terms of granting Employee Additional Income in the Bengkulu Province Government are calculated based on the determination of job weight, work performance and employee discipline, as stated in the Bengkulu Province Regulation concerning Giving Additional Income to Bengkulu Province Government Employees; and (2) Mechanisms for granting Employee Additional Income within the Bengkulu Province Government have been carried out according to operational standards for improving employee welfare in the Bengkulu Province Government, namely based on Bengkulu Province Regulation concerning Giving Additional Income to Bengkulu Province Government Employees.